ASSESSMENT OF THE QUALITY OF CRUDE PALM OIL FROM ELAEIS GUINEENSIS GROWING AREAS OF THE PT. LANGKAT NUSANTARA KEPONG-PTPN II NORTH SUMATERA - Ida Duma Riris; Albinus Silalahi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
Palm oil is one of the major fats and oils produced in Indonesia, which is of great value in the diet of many people. The quality of palm oil could be affected by various factors ranging from improper postharvest handling, processing and storage. Recently, there has been wide spread speculation that palm oil is adulterated in order to maximize profit (Madubuike et al., 2015). The quality parameters of palm oil are generally determined by the moisture content, impurity, specific gravity, percentage of free fatty acid (FFA), iodine value, peroxide value and saponification values. The objective of this research therefore was to evaluate the quality of palm oil samples obtained from elaeis guineensis growing areas of the PT. Langkat Nusantara Kepong-PTPN II North Sumatera. The results showed that mean value of the quality parameters are 0.15% moisture content; 5.71% impurity level; 0.935 specific gravity;8.43% FFA; 52.13 iodine value; 13.71meq/kg peroxide value; and 181,89 mg KOH/g saponification value. The quality parameters are associated with the method of processing.Keywords: Moisture Content, Impurity, Specific Gravity, Percentage Of Free Fatty Acid, Iodine Value, Peroxide Value And Saponification Values.